2012
DOI: 10.7237/sjarm/259
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and Carbon Content Allocation of Six-year-old Anisoptera Costata Korth., nd Dalbergia Cochinchinensis Pierre, Plantations in Lao PDR

Abstract: The objective of our study was to examine the biomass and carbon contents (including soil) of two six-year-old native species, Anisoptera costata and Dalbergia cochinchinensis. Forest plantation is an important strategy to restore degraded forest ecosystem not only for increasing timber supply, but also for socio-economics, environmental and biodiversity purposes. In addition, forest plantations helps to increase the biomass density and carbon content besides improving soil conditions. Increasing forest planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, comparable results were found in Siamese rosewood plantations in Lao PDR, with an MAI calculated from DBH of 0.63 cm year -¹ and from height as being 0.53 m year -1 . Results from the same study reported a survival rate after 6 years of planting of 67.5% (Phongoudome et al 2012). As a result of age, DL (15 years old) had a higher growth rate than PNK (53 years old) plantations as estimated from all parameters.…”
Section: Average Size and Mai Of Siamese Rosewood At Various Plantationsmentioning
confidence: 84%
“…However, comparable results were found in Siamese rosewood plantations in Lao PDR, with an MAI calculated from DBH of 0.63 cm year -¹ and from height as being 0.53 m year -1 . Results from the same study reported a survival rate after 6 years of planting of 67.5% (Phongoudome et al 2012). As a result of age, DL (15 years old) had a higher growth rate than PNK (53 years old) plantations as estimated from all parameters.…”
Section: Average Size and Mai Of Siamese Rosewood At Various Plantationsmentioning
confidence: 84%